1990
DOI: 10.1037/0735-7036.104.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Handedness as a function of sex and age in a large population of Lemur..

Abstract: A population of 194 lemurs (Lemur spp.), 116 males and 78 females, from 1 to 30 years of age, was assessed for lateralized hand use in simple food reaching with a minimum of 100 reaches per animal. A hand preference was present in 80% of the population with a bias for use of the left hand that was most characteristic of male lemurs and young lemurs. The results confirm the presence of lateralization in prosimians, and we interpret the sex and age differences in relation to current theories of neural lateraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
83
8
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(120 citation statements)
references
References 13 publications
26
83
8
3
Order By: Relevance
“…Likewise, there is no significant hand preference at the population level even when a less stringent a 5 0.01 is used. Our results are in line with other NWM species (see Papademetriou et al [2005] for review) and are also consistent with other suborders which show no population bias toward lateralization of manual function (Prosimians [Cantalupo & Ward, 2000;Dodson et al, 1992;Sanford et al, 1984;Ward & Cantalupo, 1997;Ward et al, 1990]; OWM [Aruguete et al, 1992;Beck & Barton, 1972;Harigel, 1991;Rigamonti et al, 1998;Teichroeb, 1999;Westergaard et al, 2001]; and Apes [Byrne & Byrne, 1993;Colell et al, 1995;Hopkins et al, 1994;Rogers & Kaplan, 1996]). Our results are consistent with the notion that although some species show population level hand bias for specific activities, it is a uniquely human feature to show population level hand preference across a range of different behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, there is no significant hand preference at the population level even when a less stringent a 5 0.01 is used. Our results are in line with other NWM species (see Papademetriou et al [2005] for review) and are also consistent with other suborders which show no population bias toward lateralization of manual function (Prosimians [Cantalupo & Ward, 2000;Dodson et al, 1992;Sanford et al, 1984;Ward & Cantalupo, 1997;Ward et al, 1990]; OWM [Aruguete et al, 1992;Beck & Barton, 1972;Harigel, 1991;Rigamonti et al, 1998;Teichroeb, 1999;Westergaard et al, 2001]; and Apes [Byrne & Byrne, 1993;Colell et al, 1995;Hopkins et al, 1994;Rogers & Kaplan, 1996]). Our results are consistent with the notion that although some species show population level hand bias for specific activities, it is a uniquely human feature to show population level hand preference across a range of different behaviors.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have suggested a trend of right hand use increasing with age Mason et al, 1995;Ward et al, 1990]. In this study, age was not correlated with direction of hand preference as calculated by HI scores or strength of hand preference as calculated by ABS-HI scores.…”
Section: Discussioncontrasting
confidence: 68%
“…Specifically, our data indicate that female chimpanzees demonstrate greater right-hand bias in hand-to-mouth. In prosimians, a greater prevalence of right-handedness has been reported for simple reaching (Milliken, Stafford, Dodson, Pinger, & Ward, 1991;Ward et al, 1990). No sex differences have been reported for simple reaching in monkey species (Fagot & Vauclair, 1991) but greater self-mouthing has been reported for 1-day-old rhesus monkeys (Champoux & Suomi, 1988).…”
Section: Discussionmentioning
confidence: 94%